CFD modeling for the flow of fly ash slurry in straight pipeline. (2022) - Nagar, Harendra; Gupta, Tushar; Kumar, Navneet
Abstract: In this research work, CFD simulations were done for the predication of pressure drop and concentration profiles for better understating of 25 µm fly-ash particles mixed with water in the form of solid-liquid slurry in 50 mm pipe diameter with efflux concentrations in the range of 33–47 percent by volume at different flow velocities as 1–3 m/s. The Eulerian two-phase model of Ansys Fluent software was applied for computional simulations to check the complex flow pattern at higher solid concentration of fly-ash slurries. Pressure drop and concentration profiles were predicted and evaluated in relation to actual flow parameters to investigate the flow patterens of solid-liquid flow. This work is also important in the design of a slurry pipeline.